Pengaruh Hedonic Motivation terhadap Impulsive Buying pada Mahasisiwi Pengguna Platform Tiktok Shop di Kota Padang - Patrisia, Darti (Lembaga Yasin AlSys, 2024)
Nowadays most of the people spend their time checking social media accounts, and always want to stand out from other individuals. Individuals who always feel the urge to buy something show a tendency towards hedonic motivation. However, purchases made excessively are called impulsive buying. The aim of this research is to determine the effect of hedonic motivation on impulsive buying among female students using the TikTok shop platform in Padang City. This research uses quantitative methods with a correlational quantitative design. The population in this research is female students in Padang City. The sampling technique used purposive sampling technique with a total of 174 people. This research instrument is a hedonic motivation scale based on aspects from (López et al., 2016) and uses the impulsive buying scale used from (Juswan, 2022). The results of the analysis using simple linear regression data analysis obtained a correlation coefficient (R) = 0.832 with a significant value of 0.000 (P<0.05) and an influence of 69.2%, meaning that there is a significant positive influence of hedonic motivation on impulsive buying. female student using the TikTok Shop Platform.